2012
DOI: 10.1136/ejhpharm-2012-000074.366
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapeutic follow-up in oncology

Abstract: Background Morbidity and mortality associated with the use of medicines is a great problem of public health. The pharmacist has a key role in detection, preventing and resolving drug-related problems (DRP). This is even more important in the case of cancer patients, where the high number of treatment protocols and the extensive supportive therapy increases the number of drugs used. This particular setting is a challenge to the clinical pharmacist. Purpose Analysis and characterisation of pharmacotherapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
2
3
0
1
Order By: Relevance
“…26 Previous studies show that patients with chronic disease experience at least one DRP during drug treatment, and this can vary between 0.58 and 0.87 in patients with cancer. [27][28][29] The results of this study are consistent with previous published studies in many Table 3. Targeted and/or immunotherapy related DRPs according to the PCNE v.7.…”
Section: Discussionsupporting
confidence: 92%
“…26 Previous studies show that patients with chronic disease experience at least one DRP during drug treatment, and this can vary between 0.58 and 0.87 in patients with cancer. [27][28][29] The results of this study are consistent with previous published studies in many Table 3. Targeted and/or immunotherapy related DRPs according to the PCNE v.7.…”
Section: Discussionsupporting
confidence: 92%
“…Interactions with other medications can cause small changes in the pharmacokinetics or pharmacodynamics of a chemotherapy agent that could significantly alter its efficacy or toxicity. 16,17 In our study we observed 1.85% drug interaction to the total number of DRPs. While the exact incidence of Drug-drug interactions (DDI) is unknown in cancer patients, it has been estimated that about one-third of cancer outpatients are at risk of developing a DDI.…”
Section: Discussionsupporting
confidence: 53%
“…13 But a higher number of DRPs was detected in this study when compared with another retrospective study done in Portugal that detected 43 DRP in 56 patients. 14 This variation indicates that as such comparisons are hampered by different settings, measurement methods and classification systems. In this current study, nausea and vomiting occurred in 155 patients of which about 140 patients needed additional medication as an antiemetic when they subjected to highly emetic chemotherapy like platins and commonly prescribed antiemetics were Ondansetron (8-16 mg), Dexamethasone (20 mg) and Aprepitant (125 mg).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Several studies address prescription errors in oncology services and emphasize the role of the pharmacist even showing economy for health services. [9][10][11] However, there is little information on the classification of the pharmaceutical interventions (PIs) performed in this field.…”
Section: Introductionmentioning
confidence: 99%